How well do services for young people with long term conditions deliver features proposed to improve transition? - A. Colver; R. Pearse; R. M. Watson; M. Fay; T. Rapley; K. D. Mann; A. Le Couteur; J. R. Parr; H. McConachie; on behalf of the Transition Collaborative Group (BMC, 2018)
Abstract Background For young people with long-term conditions, transition from child to adult-oriented health services is a critical period which, if not managed well, may lead to poor outcomes. There are features of transition services which guidance and research suggest improve outcomes. We studied nine such features, calling them 'proposed beneficial features': age-banded clinic; meet adult team before transfer; promotion of health self-efficacy; written transition plan; appropriate parent involvement; key worker; coordinated team; holistic life-skills training; transition manager for clinical team. We aimed to describe the extent to which service providers offer these nine features, and to compare this with young people's reported experience of them. Methods A longitudinal, mixed methods study followed 374 young people as their care moved from child to adult health services. Participants had type 1 diabetes, cerebral palsy or autism spectrum disorder with additional mental health difficulties. Data are reported from the first two visits, one year apart. Results Three hundred four (81.3%) of the young people took part in the second visit (128 with diabetes, 91 with autism, 85 with cerebral palsy). Overall, the nine proposed beneficial features of transition services were poorly provided. Fewer than half of services stated they provided an age-banded clinic, written transition plan, transition manager for clinical team, a protocol for promotion of health self-efficacy, or holistic life-skills training. To varying degrees, young people reported that they had not experienced the features which services said they provided. For instance, the agreement for written transition plan, holistic life-skills training and key worker, was 30, 43 and 49% respectively. Agreement was better for appropriate parent involvement, age-banded clinic, promotion of health self-efficacy and coordinated team at 77, 77, 80 and 69% respectively. Variation in the meaning of the features as experienced by young people and families was evident from qualitative interviews and observations. Conclusions UK services provide only some of the nine proposed beneficial features for supporting healthcare transition of young people with long term conditions. Observational studies or trials which examine the influence of features of transition services on outcomes should ensure that the experiences of young people and families are captured, and not rely on service specifications.